ANALISIS TINGKAT KOMPONEN DALAM NEGERI (TKDN) TERHADAP IKLIM INVESTASI ENERGI SURYA DI INDONESIA - Ravianti, Dinnar Ajeng (Fakultas Hukum Universitas Kristen Indonesia, 2024)
This research aims to analyze the impact of Domestic Component Level (DCL) on the investment climate in the solar energy industry in Indonesia, with a focus on the regulatory framework set forth by the Ministry of Industry Regulation No. 23 2023. As the global solar energy industry grows, Indonesia has committed to developing solar energy as part of efforts to achieve clean and sustainable energy targets. Ministry of Industry Regulation No. 23 2023 plays a crucial role in setting the DCL requirements that stakeholders in the solar energy industry must meet. This research will delve into the impact of compliance with DCL requirements in terms of investment, local production, and the growth of the solar energy industry in Indonesia. Furthermore, we will evaluate the extent to which these regulations align with national goals to reduce dependence on fossil fuels and support the development of renewable energy sources.